Final purchase and trade-in decisions in response to a component phase-out announcement: a deterministic analysis. Issue 5 (3rd March 2016) - Cole, Dwayne; Kazaz, Burak; Webster, Scott
Abstract : We investigate a problem faced by a durable goods manufacturer of a product that is no longer manufactured but still under warranty. A supplier announces that a component of the product will be phased out and specifies a deadline for the final order. A common response in traditional practice is to place a final order sufficient to cover future warranty claims. We analyse and compare this policy with two policies that use trade-in programmes to supplement the final order quantity: (i) A full trade-in policy where the firm issues a one-time offer to the entire population that has the product under warranty, and (ii) a matching trade-in policy where the firm issues a trade-in offer to a fraction of the warranty population in each period. Our analysis of a deterministic model leads to two main conclusions. First, we find that the savings from the use of a trade-in programme can be significant, and we identify easy-to-estimate measures that drive the magnitude of savings. Second, we find that a full trade-in policy is likely to be preferred over a matching trade-in policy. The policy is also easier and more practical to implement. However, if uncertainty in warranty demand is introduced, then a firm may benefit by combining elements of both policies – an initial offer to a sizable fraction of the warranty population followed by periodic offers to remaining segments over time.